Survei Pembinaan Prestasi Atlet Bolabasket Kelompok Umur di Bawah 16 dan 18 Tahun Pada Tim Bolabasket Kota dan Kabupaten Madiun Tahun 2018 - Nugraha, Pratama Dharmika; Pratama, Enggel Bayu (UIR Press, 2019)
This study aimed to know the coaching achievement of Basketball athletes which age category under 16 and 18 years old of Basketball team of Madiun city and Madiun regency. This research method was descriptive design which triangulated data from observation, interview and documentation. The participants of this research were committees, coaches and athletes of Basketball team of Madiun city and Madiun regency. This research result shown that coaching practices in Madiun city are runned good enough even though they cannot maximize their effort to get achievements. Besides, for Basketball team of Madiun regency, they have not been managed by the Basketball organization of Madiun regency for 10 years ago, so they did not get coaching practice yet in regency level.